2002
DOI: 10.1016/s1010-7940(02)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Thirteen years follow-up after radical transsternal thymectomy for myasthenia gravis. Do short-term results predict long-term outcome?1

Abstract: Our data confirm that radical, transsternal thymectomy is an effective and safe therapeutic modality for MG. Short-term results seem to deteriorate over time, therefore long-term studies for minimally invasive approaches have to prove equal results before replacing the standard procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
0
31
0
4
Order By: Relevance
“…On the other hand, Huang et al [12] reported that the rates of complete remission increase in years but remain stable after the fourth year. Despite the reports of increased rates of remission, Roth et al [22] determined some relapses many years after the operation but found no significant differences between the short-term and long-term outcomes. In the same study, 90% of the patients who were followed up for 13 years, reported satisfaction with their life quality, and 65% returned to their full time jobs, and 61% reported that they were capable of doing sports such as horseback riding, walking, and swimming regularly.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, Huang et al [12] reported that the rates of complete remission increase in years but remain stable after the fourth year. Despite the reports of increased rates of remission, Roth et al [22] determined some relapses many years after the operation but found no significant differences between the short-term and long-term outcomes. In the same study, 90% of the patients who were followed up for 13 years, reported satisfaction with their life quality, and 65% returned to their full time jobs, and 61% reported that they were capable of doing sports such as horseback riding, walking, and swimming regularly.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that the factors causing the disease are not completely eliminated with thymectomy, but the number of causative factors were reduced or their effects were suppressed. Failure to obtain optimal outcomes after thymectomy procedure have been attributed to several factors, such as incomplete thymectomy, irreversible neuromuscular joint damage, presence of the peripheral lymphoid nodules and spleen that can have thymic effects, presence of peripheral T cells with long life, and heterogeneous disease mechanism (different thymic effects on patients) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Thymectomy has been shown to be effective in treating TETs with concomitant MG before surgery, with an improvement rate of 73% to 89%, and a complete remission rate ranging from 28% to 52% (8,(15)(16)(17)(18). Studies to date mainly compared the therapeutic effects of surgery with medical treatment (cholinesterase inhibitors and immunosuppressive agents), with favorable results showing higher improvement rates in patients who received thymectomy than medical treatment (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date mainly compared the therapeutic effects of surgery with medical treatment (cholinesterase inhibitors and immunosuppressive agents), with favorable results showing higher improvement rates in patients who received thymectomy than medical treatment (16,17). Up till now, no study has ever compared the effect of the extent of thymectomy on the outcome of surgical treatment for MG with concomitant thymomas.…”
Section: Discussionmentioning
confidence: 99%
“…Myastenia Gravisin tedavisi medikal ve cerrahi tercihleri içermek-tedir. Alta yatan otoimmün mekanizmada asetilkolin reseptörlerine yönlenen spesifik antikorların üretilmesi, oluşan komplekslerin etkisiyle fonksiyonel ve sayısal olarak bu reseptörlerin azalması bulunmaktadır (2). Sahip olduğu fonksiyon ve rollerle timusun bu patogenezde ayrılmaz bir yer aldığını düşünülmektedir.…”
Section: Introductionunclassified